A snapshot of ABO, RH, and JK blood group systems in modern Ireland. Issue 2 (12th June 2021) - Browne, Anne; Kinsella, Anthony; Keogh, Moira; Morris, Kieran; Field, Stephen
Abstract: Objectives: This study aimed to capture a snapshot of the Irish population to determine if there had been any changes in the ABO and RH blood group system (BGS) distribution from previous Irish studies and to establish an Irish JK BGS frequency, providing real time donor information to the Irish Blood Transfusion Service (IBTS). Background: Ireland's population is constantly increasing and becoming more diverse, this has potential implications for the IBTS to provide blood with extended phenotypes for certain cohorts of patients. Materials and methods: All first time blood donors had relevant testing performed in the Automated Donor Grouping (ADG) laboratory using the Beckman Coulter PK7300 analyzer with appropriate antisera by validated methods. All pertinent information and test results were categorized and analyzed. Results: The number of donors tested was 3427. ABO phenotype: A: 29.82%, B: 12.02%, O: 54.95% and A, B: 3.21%. RHD: 82.26%. RHCE: R1 R1 : 17.62%, R2 R2 : 2.89%, R1 R2 : 13.95%, R1 r: 33.35%, R2 r: 13.07%, Ro r: 1.25%, R1 RZ : 0.06%, R2 RZ : 0.06%, r′r: 0.55%, r″r: 0.53%, rr: 16.66%. Kidd phenotype: Jk(a + b+): 49.63%, Jk(a‐b+): 23.34%, Jk(a + b‐): 27.02%. Conclusion: The observed frequencies for the relevant BGSs remained relatively unchanged to the prevalence values expected; however, statistically significant differences between the 2015 study and some of the previous studies were found for ABO distribution. 14.24% of the first time donors were born outside Ireland and statistically significant differences ( P ‐value < 0.001) were noted for aspects of the ABO and Rh phenotype distribution for the Irish born donors (BiI) vs those born outside Ireland (BoI).